Implementation Of The Jigsaw Method To Improve Reading Comprehension Students’ Seventh Grade At SMP NU Karaban In Academic Year 2023/2024 - Febri Khoirunnisa’ (Pusat Riset dan Inovasi Nasional, 2023)
Reading activity has many benefits especially for students in discovering and understanding knowledge during the learning process. In the reading process, students also need to understand the text they read. Reading discussion is a series of activities or processes carried out by readers to gain an understanding of what they are reading and aimed at obtaining information that is interesting to readers. There are several methods used to improve students' understanding of reading, one of which is the jigsaw method. Jigsaw has gained popularity as a method of learning English, especially in reading understanding. This research uses pre-experimental quantitative methods. The ceremony was held at SMP NU Karaban, located in the Karaban Village, Pati district, Central Java. This research was conducted through the following procedures: giving pre-test, treatment, and giving post-test. Data collected by tests. The results showed that there was a significant difference between the pre-test and post-test scores.. It can be seen from the data analysis using the t-test with a significance level of 5%. The result of the hypothesis is 0.000<0.05, indicating that the t-value <t-table. So, Ho is rejected, and Ha is accepted. The mean pre-test score of students was 69.39, and the mean post-test score of students in the experimental group was 88.39. So, it can be concluded that there is a significant difference between students' reading comprehension taught by using the Jigsaw Method.In the learning process using the Jigsaw method shows that students are very enthusiastic, active and also collaborative towards their goals